2003
DOI: 10.1007/s00244-002-2120-4
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Other Trace Elements in Sediment Cores from Central Texas Lakes

Abstract: Metals released during fossil fuel use are important atmospheric pollutants. Mercury and other trace metals can be transferred to an aquatic environment through atmospheric deposition. In the work reported here, a number of sediment cores were retrieved from central Texas lakes in the proximity of a coal-fired power plant in search of local anthropogenic effects. Cores were collected along a transient parallel to the prevailing wind direction (S-SE) in the area. Trace element concentrations in the lignite and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Therefore, at this time, the most reliable way to understand the impacts of coal-fired power plants on Hg deposition is based on empirical data. In terms of excesses over background, local soil concentration Hg increments are around 30%-60%; sediment increments are 18-30% (Anderson et al 1977, Menounou et. al.…”
Section: Evidence From the Literature For "Hot Spots" Near Mercury Emmentioning
confidence: 98%
“…Therefore, at this time, the most reliable way to understand the impacts of coal-fired power plants on Hg deposition is based on empirical data. In terms of excesses over background, local soil concentration Hg increments are around 30%-60%; sediment increments are 18-30% (Anderson et al 1977, Menounou et. al.…”
Section: Evidence From the Literature For "Hot Spots" Near Mercury Emmentioning
confidence: 98%
“…Mercury from lakes throughout the US ranged from 30 to 330 ng/g (Menounou and Presley 2003;Huggett et al 2001;Cooper and Gillespie 2001;Sorensen et al 1990;He et al 2007) and varied greatly across regions. No previously published studies of mercury content in wetlands or ponds in Illinois were found.…”
Section: Sediment Mercurymentioning
confidence: 99%
“…The suspended and precipitated substances eventually settle down at the bottom and serve as a reservoir for trace substances of low solubility, low degree of degradability and many pollutants [14][15][16]. Information related to natural and anthropogenic influence on the water bodies, which is environmentally significant, can be obtained from the chemical analysis for characterization of sediments [17][18][19][20][21][22]. Thus, to evaluate the quality of total ecosystem of a water body, in addition to the water sample analysis, the analysis of sediment is of equal importance [23-31].…”
Section: Introductionmentioning
confidence: 99%